Crystallization of gray cast irons - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2025)
Crystallization of gray cast irons is a nanostructured process in which nanocrystals of iron, silicon and graphite play a major role. Austenite microcrystals are not solid solutions of silicon and carbon atoms in the γ‑Fe crystal lattice. In the crystallization of gray cast irons, oxygen and hydrogen atoms are demodifying elements of the austenite structure. In the crystallization of gray cast irons, oxygen, hydrogen and sulfur atoms are demodifying elements of the graphite structure. Molecular hydrogen released on dendritic austenite microcrystals prevents their branching, contributing to the demodification of the austenite structure. The modifying elements of gray cast irons reduce the concentrations of demodifying elements in the melts, contributing to the formation of branched dendritic graphite microcrystals.